2014
DOI: 10.1177/0306624x14561430
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Two-, Three-, and Four-Factor Structures of the Korean PCL-R in Serious Offenders

Abstract: There is no published work on different factor structures of the Psychopathy Checklist-Revised (PCL-R) for Korean offenders. The current study compared the two-, three-, and four-factor structures of the Korean version of the PCL-R. A total of 451 adult male serious offenders were included. The results suggested that both three- and four-factor models offered the best overall fit to the data. To gain better insight into the construct and predictive validities of the Korean version of the PCL-R, we recommend fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The findings in this South Korean sample need to be placed within the context of the extremely limited prior work on the PCL‐R conducted in Korea. Sohn and Lee (2016) focusing on psychometric properties of the PCL‐R found support for both three‐ and four‐factor models, with a slightly better fit for a three‐factor model, which parallels the findings in Flórez et al (2018) and Skeem and Cooke (2010). Sohn et al (2017) utilized 3‐year reconviction data to assess the utility in predicting 87 general recidivists compared to 364 nonrecidivists and found that facet 3 (lifestyle) best predicted general recidivism.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The findings in this South Korean sample need to be placed within the context of the extremely limited prior work on the PCL‐R conducted in Korea. Sohn and Lee (2016) focusing on psychometric properties of the PCL‐R found support for both three‐ and four‐factor models, with a slightly better fit for a three‐factor model, which parallels the findings in Flórez et al (2018) and Skeem and Cooke (2010). Sohn et al (2017) utilized 3‐year reconviction data to assess the utility in predicting 87 general recidivists compared to 364 nonrecidivists and found that facet 3 (lifestyle) best predicted general recidivism.…”
Section: Discussionsupporting
confidence: 66%
“…Inter-rater reliability between two separate evaluators ranged from .79 to .91 (Cho & Lee, 2008). Both construct and predictive validity have been reported previously (Sohn & Lee, 2016;Sohn et al, 2017).…”
Section: The Korean Pcl-r (2008)mentioning
confidence: 68%
“…Naturally, there are some concerns with the accuracy and validity of this type of data. As suggested by Sohn and Lee [51], presumably, such differences in the legal and judiciary systems of Korea and the UK may have affected this result or influenced the dynamics of these items.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, other comparison studies with female offenders' samples (Eisenbarth et al, 2018) pointed to the superiority of a four-factor model of psychopathy. Furthermore, a study conducted among Korean serious offenders comparing the two-, three-, and four-factor structures of the PCL-R revealed that both the three-and four-factor models offered, overall, the best fit to the data (Sohn & Lee, 2016).…”
Section: Introductionmentioning
confidence: 99%